Identification and Isolation of Microalgae from Pond Waters in Pekanbaru City - Hatmidah Hatmidah; Eddiwan Eddiwan; Efawani Efawani (Berkala Perikanan Terubuk, 2022)
Microalgae live in almost all types of waters, including in groundwater. The diversity, fertility, and development of microalgae species in ponds are strongly influenced by the conditions and fertility of the waters. This study aims to determine the types of microalgae found in the Pekanbaru City Pond Waters. This research was conducted in Aquatic Biology Laboratory Faculty of Marine and Fisheries, Riau University by survey method. Sampling locations consist of 4 stations and 3 sampling points. The results showed that there were 13 species of microalgae found in ponds in Pekanbaru City, namely: Scenedesmus quadricauda, Pediastrum duplex mey, Tetrastrum heteracarthum, Spirulina platensis, Microcystis aeruginosa, Chlorella vulgaris, Scenedesmus dimurphus, Pediastrum duplex var, Closeterium parvulum, Coelastrum microforum, Scenedesmus acuminatus, Pediastrum biradiatum and Scenedesmus obligus. Based on laboratory culture results, the highest abundances of microalgae were Scenedesmus quadricauda, Spirulina plantensis and Chlorella vulgaris.